Antisemitism among adolescents in Germany - Schröder, Carl Philipp (Youth and globalization, 2020)
Europe is facing a new wave of antisemitism, which has grown in recent years. In 2019, the number of reported antisemitic crimes has increased in Germany. On the one hand, Muslim immigrants are suspected of so-called “imported Antisemitism”. On the other hand, right-wing extremism still appears to be the main cause of most antisemitic crimes. Moreover, antisemitism may also be rooted in the left-wing spectrum hiding behind the criticism of Israel and its policies. To analyze the connections of antisemitic attitudes, data from a school survey of 6,715 ninth-graders are used. The results indicate a strong connection between right-wing attitudes and antisemitism as well as left-wing and Islamist attitudes and antisemitism. Higher values of antisemitism are also found among Muslims, but the main predictor of antisemitic attitudes is by far right-wing attitudes.